1967
DOI: 10.1002/j.1537-2197.1967.tb10699.x
|View full text |Cite
|
Sign up to set email alerts
|

The Chloroplast Structure of Iojap Maize

Abstract: The ultrastructure of the plastids from the genetically caused but maternally transmitted mutant iojap of maize was studied at four stages of development. The plastids of green and potentially green tissue were normal at all stages studied. The plastids of the white tissue were aberrant at all stages studied and lacked the normal grana‐fretwork system as well as a normal prolamellar body. DNA‐like fibrils were present in aberrant plastids, but ribosomes were absent. This indicates that chloroplast ribosomes ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0

Year Published

1968
1968
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 14 publications
3
27
0
Order By: Relevance
“…We concluded that the ATPase isolated from the maize plastid membranes is identical with the coupling factor CF1. The absence or, at least, the very low content of fraction I protein and of plastid coupling factor CF1 in the white tissue of +/y maize confirms an earlier electron microscopic observation that the white plastids of this mutant contain no ribosomes (14). White plastids of +/ij maize were reported to contain no rRNA and to have no ability to incorporate amino acids into protein (15).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…We concluded that the ATPase isolated from the maize plastid membranes is identical with the coupling factor CF1. The absence or, at least, the very low content of fraction I protein and of plastid coupling factor CF1 in the white tissue of +/y maize confirms an earlier electron microscopic observation that the white plastids of this mutant contain no ribosomes (14). White plastids of +/ij maize were reported to contain no rRNA and to have no ability to incorporate amino acids into protein (15).…”
Section: Resultssupporting
confidence: 83%
“…Their matrix contains DNA fibrils and membranous structures, but grana thylakoids are not formed. Interestingly, no ribosomes have been observed in the affected plastids (14). The absence of ribosomes in altered plastids was recently confirmed by Walbot and Coe (15).…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…What is characteristic to leaf variegation is formation of white and green sectors in the same leaf. It means that a green tissue contains normal chloroplasts (originated from plas-tids as they develop thylakoids internally), whereas a white tissue lacks developed chloroplasts and only contains abnormal plastids (Burk et al, 1964;Shumway and Weier, 1967). The fact that a single recessive mutation can result in such a sector formation suggests that a loss of the gene function may affect the leaf cells unequally.…”
Section: Characteristic Features In Leaf-variegated Mutantsmentioning
confidence: 99%
“…In spite of the great number of papers dealing with the site of synthesis of chloroplast components published in the last years, our knowledge on this topic is still rather limited [ 1 ]. Recently, several mutants of higher plants [2][3][4][5][6] and of Chlttmydomonas [7,8] have been described in which the plastid ribosomes are either entirely lacking or only present in a low frequency. As a result of the deficiency no proteins (or only a very low amount of proteins) can be synthesized within the plastids.…”
Section: Introductionmentioning
confidence: 99%